Structured Prescriptive Models of Risk Attitudes - Harvey, Charles M. (Management Science, 1990)
This paper discusses conditions on risk attitudes that imply special types of expected-utility functions. First, conditions are described that correspond to different choices of an arithmetic operation that measures the importance of changes in consequences. Second, conditions are described such that one consequence in a pair of indifferent lotteries depends linearly on a consequence in the other lottery. Procedures are described for using one of the conditions to model the risk attitude of a public or private decision making group without performing the detailed preference assessments that are needed to determine a general utility function.